A percepção dos papéis do coordenador de curso e as expectativas da IES privada sobre esses papéis - Tittanegro, Pedro Angelo (2008)
This study arises from the need to re-think and organize the work to achieve the goals personal and institutional, as coordinator of graduate courses. The objective of this work was to contribute to the discussion on the roles of the coordinator in the course of private IES - Institutions of Higher Education. Specifically, we examine how these roles are characterized in the light of the demands of the market on the educational system. It was present: 1) the concepts on Brazilian higher education - the actual situation and the scenarios and trends - 2) the dimensions that interact in the definition of roles - such as the organizational culture, planning, decision-making, leadership , strategies, communication, in addition to the mission, institutional vision and beliefs - 3) the roles of the coordinator of course, according to two institutional managers: David F. Barros and Edson Franco, correlating them with managerial roles proposed by two authoritative researchers in management; Henry Mintzberg, Robert Quinn. Intend with this text make a few observations about the roles of the coordinator of course and practice the same, without the pretense of offering a comprehensive analysis and exclusive about this, not even define and design models. This paper was prepared by searching the literature, official documents of the MEC, the INEP and a private IES, in addition to the legislation and articles from various authors, both in the area of university management as of Education. Brings still the vision of the author on the subject, as a teacher and coordinator of higher education courses, to play such roles in IES private. It is, after analysis of texts and situations, the coordinator of course is assuming roles increasingly complex and that require a deeper implications on the performance of this work and in the definitions of institutional goals and objectives